A study on incidence and etiology of cervical lymphadenopathy in community - Chaudhary, Sonalben; Chaudhari, Sandipkumar; Patel, Jimitkumar; Patel, Bhavin (International Journal of Research in Medical Sciences, 2022)
Background: The etiologies for cervical lymphadenopathy fall under a wide range spectrum and usually, history and physical examination alone may lead to a diagnosis. Posterior cervical LAP may occur with Epstein-Barr virus (EBV) infection, tuberculosis, lymphoma, or head and neck malignancy (either lymphomas or metastatic squamous cell carcinoma). However, a stepwise methodological approach to LAP can lead to an accurate diagnosis with minimal discomfort to the patient and also less time-consuming for the clinician. Methods: In this series, 320 cases were studied with taking a detailed clinical history, physical examination, and investigations. After a physical examination and reaching a clinical diagnosis, confirmation was done by fine needle aspiration cytology (FNAC) and biopsy. Results: Incidence of tuberculous LAP is much higher in lower socioeconomic class groups people versus middle or higher socioeconomic class groups. Incidence of tuberculous LAP is higher in urban areas compared to rural areas due to overcrowding, and poor sanitation. Conclusions: Tuberculosis is a potentially serious infectious disease, one of the commonest diseases affecting lymph nodes. It is curable with anti-tubercular drugs if administered as per the accepted regimen.